PELAKSANAAN KEGIATAN USAHA BADAN USAHA MILIK DESA SUNGAI BESAR KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA - NIM. A1012201030, SAWALUDIN (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACTVillage Owned Enterprises is a business entity whose capital is wholly or largely owned by the village through direct participation originating from village assets which are separated to manage assets, services and other businesses for the greatest welfare of the village community. The lack of effectiveness in implementing Village Owned Enterprises often becomes a polemic that arises within the village community, especially if Village Owned Enterprises is in a vacuum or seems to exist and not exist. In this regard, this also happened in Sungai Besar Village, Batu Ampar District, Kubu Raya Regency. Sungai Besar Village Owned Enterprises, was formed on 01 September 2022 based on the Registration Certificate of Legal Entity Establishment of the Ministry of Law and Human Rights of the Republic of Indonesia Number: AHU-06962.AH.01.33 of 2022 with the name